IDENTIFIKASI BENTUKINTERVENSIPEMBELAJARAN DAN PERILAKU BELAJAR ANAK RETARD ASI MENTAL - Ishartiwi Ishartiwi (Jurnal Penelitian Ilmu Pendidikan, 2010)
The aim of the research is to identify the form of learning intervention and behavior of Grade III mental retardation students in Pembina Special School Yogyakarta. While the indicator of type of learning intervention is teacher' performance in educating students, the Indicator of student's learning behavior is student's responses. The information gathered in the research is collected by using in-depth observation using camera recorder. The information then analyzed by describing the fact of students' characteristics based learning process. The research indicates that: (I). There are variety types of learning intervention in the aspects of learning stimulants, materials packaging, the numbers of tasks, and teacher's positions; (2) There are variety types of student's learning behaviors in responding teachers' instruction in the aspects of learning attitudes, interests and task responses. Key words: Specific Learning Intervention, Learning Behaviour Of Mental Retarded Students, Mental Retardation.